Ultrasonic extraction method for quantifying bioavailable phosphorus in particulate form. Issue 3 (June 2017) - Ngoc, Nguyen Minh; Inoue, Takanobu; Yokota, Kuriko
Highlights: A rapid ultrasonic extraction method was proposed for quantifying particulate BAP. The bioavailability of extractable P was evaluated in algal growth potential assays. The proposed method could obtain the entire BAP fraction in a single-step extraction. The proposed extraction was lessen to 1 min whereas the conventional method required 17 h. Abstract: Eutrophication is a common problem in closed bodies of water areas during the summer. Recent reports have alleged that bioavailable phosphorus (BAP) in particulate forms contributes to eutrophication. However, current methods for quantifying particulate BAP are time-consuming and tedious. Here, we investigated the use of extraction with 0.1 M NaOH solution in combination with ultrasonication to quantify potential BAP in particulate forms in soils and suspended sediments from an agricultural area. The ultrasonic extraction process was considerably less time-consuming than conventional methods and would thus permit analysis of a greater number of samples. The bioavailability of extractable P was verified in algal growth potential assays involving P-starved Microcystis aeruginosa. The high correlation between the concentration of extracted BAP and M. aeruginosa growth at day 25 of incubation proved that the entire BAP fraction could be obtained in a single-step extraction. However, algal growth was also observed in cultures in which solid residues were the sole P source, confirming that the P left behind after extraction could be taken up by algal cells. This result suggests that in P-depleted media, algae could utilize cellular nutrients for growth. Therefore, M. aeruginosa is inappropriate for use in bioassays in P-depleted environments. Cellular mechanism of P uptake by algae should be investigated further to elucidate the factors that might limit or interfere with algal growth in nutrient-depleted environments.